Preparation, Characterization and Study Antibacterial Activity of Schiff Base and O-(Carboxyl) Chitosan Derivatives Biopolymer - Mahmood M. Ahmed (Journal of Global Pharma Technology, 2018)
Thiadiazole, Schiff bases are very important compounds used in the biological and industrial field and for this reason, chitosan has been modified with these compounds. Vehicles are prepared in the following ways. Initially, 2-amino-5-mercapto-4,3,1 tahiadiazole [1] were introduced according to the lectures through the thiosemcarbazide interaction with carbon disulphide in the presence of anhydrous sodium carbonate in absolute ethanol.2-amino-5-mercapto-4,3,1-tahiadiazole was activated with Salicylaldehyde in the presence of ethanol and a compound was obtained [2]. The compound [2] was then reacted with chloroacetic acid in the presence of anhydrous sodium carbonate in the distilled water Obtain the compound [3] .Schiff bases compounds [4-5] Attended with an Anthranilic acid reaction, 4-amino benzoic acid with benzaldehyde derivatives with absolute ethanol .The compounds [3-4], [6] were treated with chitosan (CS) for modulation and compounds [7-9].  The synthesized compounds were characterized by FTIR, 1HNMR, melting point.Keywords: Schiff base, Biopolymer, O-(carboxyl) chitosan derivatives, Antibacterial activity.